Techniczne, środowiskowe i ekonomiczne aspekty wykorzystania energii ze źródeł odnawialnych - Pindór, Tadeusz; Preisner, Leszek (Technical, Environmental and Economic Aspects of Renewable Energy Sources Use, 2009)
The analysis of the structure of energy consumption makes a base for research on technical, environmental and economic aspects of management of energy produced from primary energy sources. The paper presents the share of particular energy sources in global power and heat energy production and, in this context, energy sources management in Poland. Particular attention is paid to renewable energy production and consumption according to energy generation sources. Limits for solar energy, wind energy and geothermal energy use in Poland and on global scale are presented in the final part of the article.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 145-153